Decreased phosphatase PTEN amplifies PI3K signaling and enhances pro-inflammatory cytokine release in COPD - Yanagisawa,S; Baker,JR; Vuppusetty,C; Fenwick,P; Donnelly,LE; Ito,K; Barnes,PJ (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2017)
The phosphatidylinositol 3-kinase (PI3K) pathway is activated in chronic obstructive pulmonary disease (COPD), but the regulatory mechanisms for this pathway are yet to be elucidated. Our aim was to determine the expression and role of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), a negative regulator of the PI3K pathway, in COPD. PTEN expression and activity were measured in the peripheral lung of COPD patients compared to smoking and non-smoking controls. The direct influence of cigarette smoke extract (CSE) on PTEN expression was assessed using primary lung epithelial cells and a cell line (BEAS-2B) in the presence or absence of L-buthionine-sulfoximine (BSO) to deplete intracellular glutathione. The impact of PTEN knock-down by RNA interference on cytokine production was also examined. In peripheral lung, PTEN protein was significantly decreased in patients with COPD compared to the subjects without COPD (p < 0.001), and positively correlated with the severity of air-flow obstruction (FEV1 % predicted; r = 0.50; p = 0.0012), although no difference was observed in PTEN activity. Conversely, phosphorylated Akt, as a marker of PI3K activation, showed a negative correlation with PTEN protein levels (r = -0.41; p = 0.0042). Both in primary bronchial epithelial cells and BEAS-2B cell line, CSE decreased PTEN protein, which was reversed by N-acetylcysteine treatment. PTEN knock-down potentiated Akt phosphorylation and enhanced production of pro-inflammatory cytokines, such as IL-6, CXCL8, CCL2 and CCL5. In conclusion, oxidative stress reduces PTEN protein levels, which may result in increased PI3K signaling and amplification of inflammation in COPD.